The impact of accountability pressure and time budget on the quality of audit services of independent auditors - Hien, Nguyen Thi Thu; Tuan, Dang Anh (Edelweiss Applied Science and Technology, 2025)
Audit quality has always been a top priority in conducting audit work, as it is essential for maintaining stakeholder trust and addressing its complexities. This study examines how various auditor characteristics impact audit service quality. Primary data were collected in 2024 through a survey of 110 auditors working at independent audit firms, and the data were analyzed using SPSS 28 statistical software. The results indicate that auditor competence, independence, accountability, and time budget pressure all have a significant effect on audit service quality. Among these, auditor competence emerges as the most influential factor, followed closely by independence and accountability. This finding emphasizes the importance of competence and independence in ensuring high-quality audit work within a complex professional environment. Additionally, accountability and time budget pressure serve as catalysts that can influence whether the quality of work is high or low. From a practical perspective, these results suggest the need to enhance the quality of audit professionals and to implement mechanisms that ensure auditors maintain their independence.